Papel de SOCS2 nos comportamentos tipo maníaco e depressivo experimental: percepções das ações do tratamento com Zileuton como terapia experimental emergente para o transtorno bipolar - Katherinne Manrique Perico (2017)
Bipolar disorder (BD) pathophysiology occurs because of a complex interaction in neuroimunoendocrine system of genetic, molecular, cellular and environmental factors. Both episodes, depressive and manic, of BD were associated with immunoinflammatory factors. Zileuton is an inhibitor of the 5-lipoxygenase enzyme involved in the production of pro-and anti-inflammatory lipid mediators such as leukotrienes and lipoxins, respectively. Lipoxins modulate the expression of the protein Suppressor of Cytokine Signaling (SOCS) 2, which, in turn, regulates the signaling of cytokines and neurotrophic factors. Currently, there is no experimental model reproducing the oscillation of depression to mania presented in TB. However, mania-like behavior can be induced by GBR 12909 (selective inhibitor of dopamine transporter), being a well-accepted model of mania. The role of SOCS2 and eicosanoids in TB is not known and its elucidation is the main objective of this study. C57BL6 (C57BL6) and SOCS2 Knock-out (KO) mice were administered with GBR 12909 or saline and Zileuton or vehicule, and the presence of mania was assessed by hyperlocomotion analysis immediately for 30 minutes or 24 hours after administration of GBR. The expression of SOCS2 and production of cytokines and neurotrophic factors were evaluated in different regions of the brain using Western Blotting, CBA (Cytometric Bead Array) and ELISA (Enzyme Linked Immuno Sorbent Assay), respectively. SOCS2 KO mice presented a depressive basal behavior and when treated with GBR 12909, despite having a delayed mania response, they were not able to control the action of GBR; since in C57BL6 the hyperlocomotion is evident after 10 minute of drug administration in SOCS2KO occurred only 25 minutes later and remained high up to 24 hours later. Our results demonstrated lower expression of SOCS2 in prefrontal cortex of the brain of GBR treated C57BL6 mice compared to untreated. Deficiency of SOCS2 resulted in increased IL6, IFNγ, MCP1, and IL10 and reduced neurotrophic factors (BDNF and GDNF). Treatment with Zileuton increased SOCS2 expression in the prefrontal cortex, but not in hippocampus, of the GBRtreated C57BL6, and reduced mania like behavior in these animals but not in SOCS2 KO. Taken together, these results suggest that administration of GBR in SOCS2 KO may be a potential experimental model for the study of bipolar disorder and that Zileuton reduces the severity of experimental mania symptoms by inducing SOCS2.